1997
DOI: 10.1017/s0950268896007315
|View full text |Cite
|
Sign up to set email alerts
|

The serotype distribution of Campylobacter jejuni and C. coli isolated from patients with diarrhoea and controls at Tikur Anbassa Hospital, Addis Ababa, Ethiopia

Abstract: Sixty-eight isolates of Campylobacter jejuni and C. coli isolated from patients with diarrhoea (n = 630) and controls (n = 220) at Tikur Anbassa Hospital, Addis Ababa, Ethiopia were serotyped on the basis of the heat-labile (HL) and the heat-stable (HS) antigens, by using 16 and 34 antisera, respectively, for the two methods. With the antisera against heat labile antigens, 89.3% of the C. jejuni and 75% of the C. coli were typable. The HL serotypes 1, 2, 3, 4, 5, 6 and 7 were the most common among the C. jejun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 27 publications
3
6
0
Order By: Relevance
“…However, this level of typeability is comparable to that from a recent study of poultry campylobacter isolates in The Netherlands where 18% of isolates were found to be untypeable by using the Penner serotyping technique (11). The most recently published data from studies using the Penner scheme for isolates from humans have been those from studies carried out in China and Japan (17) and Ethiopia (4). The quoted untypeability rates are 58.8% for Chinese isolates, 13.0% for Japanese isolates, and 63.4% for Ethiopian isolates.…”
Section: Discussionsupporting
confidence: 79%
“…However, this level of typeability is comparable to that from a recent study of poultry campylobacter isolates in The Netherlands where 18% of isolates were found to be untypeable by using the Penner serotyping technique (11). The most recently published data from studies using the Penner scheme for isolates from humans have been those from studies carried out in China and Japan (17) and Ethiopia (4). The quoted untypeability rates are 58.8% for Chinese isolates, 13.0% for Japanese isolates, and 63.4% for Ethiopian isolates.…”
Section: Discussionsupporting
confidence: 79%
“…Serotyping C. jejuni/coli strains from human patients in Etiopia, Asrat et al (1997), in accordance with other countries of the world, found the highest frequency of occurrence of serotypes HS 1, 3, 8, 26 and 34. These authors, however, found that about a quarter of strains was positive for more than 1 serotype.…”
Section: Discussionsupporting
confidence: 79%
“…The Penner's serotyping scheme uses 62 antisera (HS) at present, and the Lior's system works with 122 antisera (HL) (Asrat et al 1997). Regarding the high number of antisera it is clear that only a selected group of them is mostly used.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the predominant LG genotype of strains belonging to the HS-4 complex serogroup was only found in 38% of the strains tested. Penner serogroups 1, 2, 3, and especially 4, which together comprise a large proportion of clinical isolates in certain parts of the world, are not clonal but represent a genetically diverse population (2,13,14,19,27,32). In this respect, the strong correlation between LG genotype and HS-1, HS-2, and HS-3 serotype is remarkable.…”
Section: Discussionmentioning
confidence: 99%